Region and Memory of Literature - Schupplerová, Stanislava (Starość i młodość w literaturze i kulturze, 2016)
The article deals with region of Jeseníky, its representation in Czech prose written after 1945. Emphasisis placed on two themes — on term of region and on reflection the term in literature and memory ofliterature. We try to explain term of region and in second part we analyse prosaic texts, which thematisethis area, therefore region of Jeseníky. Our interest is focused on these Czech authors — Vladimír Körner,Josef Urban, Jaroslav Rudiš, Jaromír Švejdík.